2022
DOI: 10.2174/1386207325666220105150655
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils Restrict Diesel Exhaust Particles-induced Cell Proliferation of Lung Epithelial A549 Cells via Interleukin-13 Mediated Mechanisms: Implications for Tissue Remodeling and Fibrosis

Abstract: Background: Diesel exhaust particulates (DEPs) affect lung physiology and cause serious damage to the lungs. A number of studies demonstrated that, eosinophils play a very important role in the development of tissue remodelling and fibrosis of lungs. However, the exact mechanism of pathogenesis of tissue remodelling and fibrosis is not known. Methods: Both in vitro and in vivo models were used in the study. HL-60 and A549 cells were used in the study. Balb/C mice of 8 to 12 weeks old were used for in vivo st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Fukuoka et al demonstrated that DEP disrupted TJs, thus leading to increased permeability of nasal epithelial cells [24] and facilitating the entry of allergens into subepithelial tissues causing the exacerbation of antigenspecific IgE-bearing mast-cell-mediated immediate allergic responses. Both in vitro and in vivo studies demonstrate that DEPs trigger the proliferation of eosinophils and increase secretion of interleukin (IL)-13 on lung epithelial cells causing fibrosis and tissue remodelling in the lungs [63]. Moreover, DEP stimulation on the primary human nasal epithelium modifies the basal secretome leading to inflammation with effusion of fluids [64,65].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Fukuoka et al demonstrated that DEP disrupted TJs, thus leading to increased permeability of nasal epithelial cells [24] and facilitating the entry of allergens into subepithelial tissues causing the exacerbation of antigenspecific IgE-bearing mast-cell-mediated immediate allergic responses. Both in vitro and in vivo studies demonstrate that DEPs trigger the proliferation of eosinophils and increase secretion of interleukin (IL)-13 on lung epithelial cells causing fibrosis and tissue remodelling in the lungs [63]. Moreover, DEP stimulation on the primary human nasal epithelium modifies the basal secretome leading to inflammation with effusion of fluids [64,65].…”
Section: Environmental Factorsmentioning
confidence: 99%